Ishaq v Canada: “Social Science Facts” in Feminist Interventions - Phillips, Dana (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2018)
This article examines the role of social science in feminist intervener advocacy, focusing on the 2015 case ofIshaq v Canada (Minister of Citizenship and Immigration). InIshaq, a Muslim woman challenged a Canadian government policy requiring her to remove her niqab while reciting the citizenship oath. The Federal Court of Appeal dismissed several motions for intervention by feminist and other equality-seeking organizations, emphasizing their improper reliance on unproven social facts and social science research. I argue that this decision departs from the generous approach to public interest interventions sanctioned by the federal and other Canadian courts. More importantly, the Court’s characterization of the intervener submissions as relying on “social science facts” that must be established through the evidentiary record diminishes the capacity of feminist interveners to effectively support equality and access to justice for marginalized groups in practice.